Sustainability of the community-based ecotourism development in the Aksu-Zhabagly nature reserve, Kazakhstan: An evaluation through local residents' perception - Imanaly Akbar; Sergeyeva Aigul Maksatovna; Myrzaliyeva Zabira Kazbekkyzy; Tazhekova Akmaral Zhaksybekkyzy; Saulembaev Altynbai Tagabayevich; Mominov Serik Abdukarimovich (REGION, 2022)
The development of community-based ecotourism (CBE) has the potential to preserve biodiversity and protect the environment, as well as play an important role in the socio-cultural, economic and politically sustainable development of the community. This paper assesses the implementation of CBE development and compares the sustainability of ecotourism development between the Zhabagly community and the Abaiyl community. The data is obtained mainly through the household questionnaire survey, field observations, in-depth interviews and focus group discussions. 222 representative families were surveyed with 5-point Likert scale questions in this paper including 166 Zhabagly and 56 Abaiyl participants. The study used 18 indicators based on 4 dimensions: environmental, socio-cultural, economic and political. Results from this analysis indicate that the sustainability of CBE development in two communities is slightly different in all 4 dimensions. Zhabagly community is more successful in achieving sustainable CBE development than the Abaiyl community. The results reveal that the overall evaluation of the two communities on sustainability is moderate. However, both communities demonstrate that, potentially, they are politically unsustainable. As a result, we initially assert that the sustainability of CBE development in the Aksu-Zhabagly nature reserve (NR) is far from perfect. In particular, the positive economic and political impact of tourism development is not obvious. To address this shortcoming, tourism development organizations need to jointly develop a design policy for the sustainable development of CBE.
Keywords: 330; Community; Ecotourism; Sustainable development; Nature reserve; Aksu-Zhabagly; Kazakhstan